Basic psychological need experiences, fatigue, and sleep in individuals with unexplained chronic fatigue. (3rd April 2017) - Campbell, Rachel; Tobback, Els; Delesie, Liesbeth; Vogelaers, Dirk; Mariman, An; Vansteenkiste, Maarten
Abstract: Grounded in self‐determination theory, this study tested the hypothesis that the satisfaction and frustration of the psychological needs for autonomy, competence, and relatedness would relate to fatigue and subjective and objective sleep parameters, with stress and negative sleep cognitions playing an explanatory role in these associations. During a stay at a sleep laboratory in Belgium, individuals with unexplained chronic fatigue ( N  = 160; 78% female) underwent polysomnography and completed a questionnaire at 3 different points in time (i.e., after arrival in the sleep lab, before bedtime, and the following morning) that assessed their need‐based experiences and stress during the previous week, fatigue during the preceding day, and sleep‐related cognitions and sleep during the previous night. Results indicated that need frustration related to higher stress, which in turn, related to higher evening fatigue. Need frustration also related to poorer subjective sleep quality and shorter sleep duration, as indicated by both subjective and objective shorter total sleep time and subjective (but not objective) longer sleep latency. These associations were accounted for by stress and negative sleep cognitions. These findings suggest that health care professionals working with individuals with unexplained chronic fatigue may consider focusing on basic psychological needs within their therapeutic approach.